PENGARUH MEDIA FLANNELGRAPH TERHADAP EMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI PAUD KEMUNING KECAMATAN TENAYAN RAYA PEKANBARU - Mutmainnah '; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect on the ability of media flannelgraph Early reading in children aged 5-6 years in early childhood Kemuning district Tenayan Raya Pekanbaru. The population in this study is PAUD Kemuning district Tenayan Raya Pekanbaru totaling 14 children, the sample in this study were 14 children. the method used is the experimental approach to research that seeks influence of other variables in a controlled environment is strong. This type of instrument used in this study is the use of observation and dokumentassi to take notes about events that occurred during the treatment given, the tool used is a camera. Data analysis technique using large-scale testing and analysis of statistical methods with SPSS for windows ver 17. Based on the results obtained by testing the hypothesis that there is an influence on the ability to read media flannelgraph onset in children aged 5-6 years in early childhood Kemuning district Tenayan Raya Pekanbaru. Retrieved tcount of 31.639 with a significance of 0.00. Ttabel values obtained with df 13 at 0.00 significance level of 1.771. Thus known thitung 31.639 or 0,00 significance. It has been suggested that there are significant differences in the results between the pretest and posttest. It is known that the result of higher than pretest posttest which can be seen from the descriptive statistical variable. This point can be known from the value of the correlation coefficient (r) of 0.960 with a coefficient of determination (r2) of 92.16% means it is the media's influence on the ability flannelgraph Early reading is equal to (p) = 27.5%, which is at the low category.Key words: Literacy, Media Flannelgraph